The effect of nifedipine on the patency of microvascular anastomosis in rats - Panagiotopoulos, K. E; Koutsouris, M; Panagiotopoulos, E; Antonopoulos, D; Panagiotopoulos, V; Papalois, A; Kepenekidis, A (Acta chirurgiae plasticae (English ed.), 2008)
Despite advances in microsurgical technique and experience in clinical microvascular surgery, there remains the possibility of vessel thrombosis. Factors that may contribute to vascular pedicle thrombosis include operative trauma, pedicle malposition, kinking, hypercoagulability and arterial vasoconstriction. The purpose of this study was to evaluate the effect of intravenous administration of nifedipine on the patency of the microvascular anastomosis of the femoral artery in rats. A total of 60 rats were used and divided into three groups. The first group (A) was used as a control group with no medical agent, the second group (B) was medicated with heparin, and the third group (C) was medicated with nifedipine. Patency was assessed with the distal empty refill test, one hour (1) and forty-eight hours (48) after completion of the anastomosis. The nifedipine and heparin treated groups (B & C) did not show higher patency rate compared to the control group (A). There was no statistically significant difference of patency percent after 1 hour and 48 hours among the three groups (p=0.231/p=0.480). Intravenous administration of nifedipine does not improve the patency of microvascular anastomosis. Surgical technique remains the most important factor for successful microvascular anastomosis.
Keywords: potkani Wistar; Embolism and Thrombosis; Arteriovenous Anastomosis; Vascular Patency; nifedipin; Nifedipine; heparin; interpretace statistických dat; arteriovenózní anastomóza; Data Interpretation, Statistical; průchodnost cév; Microsurgery; mikrochirurgie; Rats, Wistar; embolie a trombóza; Heparin